The complete mitochondrial genome of the freshwater snail Cipangopaludina ampullacea (Küster, 1852) (Gastropoda: Viviparidae). Issue 9 (2nd September 2022) - Wu, Meng-Meng; Cheng, Hui-Zhong; Li, Li-Li; Xie, Guang-Long
Abstract: Cipangopaludina ampullacea (Küster, 1852) is a freshwater snail endemic to China. In this study, the complete mitochondrial genome of C. ampullacea was sequenced using next-generation sequencing. The mitogenome is 16, 892 bp long and comprises a total of 37 genes, including 13 protein-coding genes, two rRNA genes, and 22 tRNA genes. It is consistent with the basic characteristics of other known viviparid mitochondrial genomes. Phylogenetic analysis using related species mitogenomes showed that Cipangopaludina and Margarya are mutually non monophyletic. Our study provides valuable information to reconstruct the taxonomy and evolution of viviparid snails more comprehensively.